26 youths to undergo training in Honda Racing Academy - Borneo Post, (KK) (Borneo Post (KK), 2012)
KUALA LUMPUR : Boon Siew Honda Sdn Bhd has picked 26 youths for training and selection with the Honda Racing Academy at Universiti Utara Malaysia (UUM), Sintok Kedah.